Hydrothermal fluid characteristics of the huayuan Pb-Zn orefield: Constraints from apatite major and trace element compositions - Tan, Rui-Chang; Shao, Yong-Jun; Wei, Han-Tao; Zhang, Jun-Ke; Yu, Meng-Da; Xiong, Yi-Qu (Frontiers in Earth Science, 2023)
The Huayuan orefield in the SW Yangtze Block (SW China) is a world-class Pb-Zn orefield, with over 20 million tonnes (Mt) metal reserve. However, the Pb-Zn ore fluid source and evolution in Huayuan remain controversial. This study determined the major and trace element compositions of the newly-identified apatite from the Pb-Zn ores, using electron microprobe analysis (EMPA) and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). The apatite samples are of hydrothermal origin, and have high CaO (52.57 – 57.15 wt.%), P2O5 (39.26 – 42.88 wt.%) and F (1.82 – 3.90 wt.%) but low Cl (<0.42 wt.%) contents. The samples have total rare earth element content (ΣREE) of 74.07 – 1255.34 ppm, and they all show negative Eu and weakly positive Ce anomalies. The result suggests that the apatite was formed in an environment with decreasing oxygen fugacity, and in relatively F-rich, Cl-poor, and REE-poor ore-forming fluid. We geochemically compared the apatite from Huayuan with those from different geneses by Fisher discriminant. The result suggests that the Huayuan apatite is distinct from typical magmatic and purely hydrothermal apatite, and that the ore-forming fluids may have had multiple sources. The mixing of fluids with different origins may have triggered significant metal ore deposition.